Utilization of Audacity Media in yhe Lesson of Maharah Istima’ - Amrina Amrina; Adam Mudinillah; M Yusuf Al Ghazali (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The learning media used today are interactive media, which are caused by the changes and developments that exist at present. With these changes and developments, of course, there is also application development that we use when learning takes place, which aims to make it easier for educators and students to transfer and receive knowledge in the learning process so that educators can also develop this Audacity application in exceptional maharah learning. This study aims to describe in detail the application of Audacity in maharah istima learning. The method used in this study is a qualitative method, which qualitative method itself is a method used by analyzing at the school, where the data analyzed by the researcher must be accurate. This audacity application is in the form of interactive audio, motivating and increasing student enthusiasm in learning. Therefore, researchers chose this application as a medium of learning in learning maharah istima’